# Trig.......

I need to prove that the following is true. Thanks
(2tanx /1-tan^x)+(1/2cos^2x-1)= (cosx+sinx)/(cosx - sinx)
and thanks ...........

I tried 30º, the two sides are not equal, they differ by 1

oh , thank you Mr Reiny I'll tell my teacher this Question is Wrong .

not necessarily.

what does tan^x mean?

I want you to check what you typed here with your question.

Mr Reiny ,
I tried 30º, the two sides are equal
L.S=3.732
R.S=3.732

Yes, if the term at the bottom is tan^2 x,
you typed tan^x, and I read it as tan x

I got the proof, give me a bit of time to type it

I'm sorry Mr Reiny you are right it is tan^2x .

LS=
2tanx/(1-tan^2x) + 1/(2cos^2x -1)
= 2sinx/cosx [1/(1-sin^2x/cos^2x)] + 1/(2cos^2x -(sin^2x + cos^2x))
=2sinx/cosx [cos2x/(cos^2x - sin^2x)] + 1/(cos^2x - sin^2x) reduce to get same denominator
=2sinxcosx/(cos^2x-sin^2x) + 1/(cos^2x-sin^2x)
=(2sinxcosx + sin^2x + cos^2x)/(cos^2x-sin^2x)
= (cosx+sinx)(cosx+sinx)/[cosx+sinx)(cosx-sinx)]
=(cosx+sinx)/(cosx - sinx)
= Right Side!!!!!

thank you Mr Reiny

1. 👍
2. 👎
3. 👁

## Similar Questions

1. ### trigonometry

how do i simplify (secx - cosx) / sinx? i tried splitting the numerator up so that i had (secx / sinx) - (cosx / sinx) and then i changed sec x to 1/ cosx so that i had ((1/cosx)/ sinx) - (cos x / sinx) after that i get stuck

3. ### trigonometry

Prove: tan2x+sec2x = cosx+sinx/ cosx-sinx

4. ### Maths

Find the general solution of equation sinx + cosx = 2 (root2) (sinx)(cosx)

1. ### Math

How do I solve this? tan^2x= 2tanxsinx My work so far: tan^2x - 2tanxsinx=0 tanx(tanx - 2sinx)=0 Then the solutions are: TanX=0 and sinX/cosX = 2 sin X Divide through by sinX: we have to check this later to see if allowed (ie sinX

2. ### math;)

The equation 2sinx+sqrt(3)cotx=sinx is partially solved below. 2sinx+sqrt(3)cotx=sinx sinx(2sinx+sqrt(3)cotx)=sinx(sinx) 2sin^2x+sqrt(3)cosx=sin^2x sin^2x+sqrt(3)cosx=0 Which of the following steps could be included in the

3. ### Trig

Verify the identity: tanx(cos2x) = sin2x - tanx Left Side = (sinx/cosx)(2cos^2 x -1) =sinx(2cos^2 x - 1)/cosx Right Side = 2sinx cosx - sinx/cosx =(2sinxcos^2 x - sinx)/cosx =sinx(2cos^2 x -1)/cosx = L.S. Q.E.D.

4. ### Trigonometry.

( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! Generally these are done by changing everything to sines and cosines, unless you see some obvious identities. Also generally, it is best to start with the more complicated

1. ### Calculus

If y=3/(sinx+cosx) , find dy/dx A. 3sinx-3cosx B. 3/(sinx+cosx)^2 C. -3/(sinx+cosx)^2 D. 3(cosx-sinx)/(sinx+cosx)^2 E. 3(sinx-cosx)/(1+2sinxcosx)

2. ### Math help again

cos(3π/4+x) + sin (3π/4 -x) = 0 = cos(3π/4)cosx + sin(3π/4)sinx + sin(3π/4)cosx - cos(3π/4)sinx = -1/sqrt2cosx + 1/sqrt2sinx + 1/sqrt2cosx - (-1/sqrt2sinx) I canceled out -1/sqrt2cosx and 1/sqrt2cosx Now I have 1/sqrt sinx +

3. ### TRIG..............

Q.1 Prove the following identities:- (i) tan^3x/1+tan^2x + cot^3x/1+cot^2 = 1-2sin^x cos^x/sinx cosx (ii) (1+cotx+tanx)(sinx-cosx)/sec^3x-cosec^3x = sin^2xcos^2x.

4. ### Calculus

determine the absolute extreme values of the function f(x)=sinx-cosx+6 on the interval 0